Reddish-blue lesion of the tongue - Manveen Kaur Jawanda; Ravi Narula; Vineet Sharma; Priya Gupta (Wolters Kluwer Medknow Publications, 2019)
Although hemangioma is considered as the most common soft-tissue tumors of the head and neck, it is relatively rare in the oral cavity and uncommonly encountered by dental professionals. The occurrence of hemangiomas on the tongue is extremely rare. Changes in blood flow dynamics within hemangioma result in thrombus and phleboliths. This article presents a relatively rare and unusual case of cavernous hemangioma of the dorsum of the tongue with phleboliths in a 55-year-old male.